Neurohormonal targets in the treatment of pediatric heart failure. (June 2018) - Edelson, Jonathan B.; Rossano, Joseph W.
Abstract: The history of the clinical approach to heart failure has been notable for a series of evolving conceptual paradigms, each in an effort to explain the clinical syndrome that presents. With the recent emphasis on a neurohormonal model of heart failure, we have seen the development of new therapeutic options that target biologically active molecules to preserve myocardial function. Sacubitril-valsartan, a combined angiotensin-neprilysin inhibitor shows the greatest clinical promise, while there is less evidence to support the use of recombinant relaxin-2 or vasopressin antagonists. This article will review the history of posited mechanisms of heart failure and the impact on treatment, novel therapeutic options with neurohormonal targets, and the challenges of developing therapies for the pediatric heart failure population. Highlights: The review will highlight new medications including Sacubitril-valsartan, a combined angiotensin-neprilysin inhibitor that shows great clinical promise, and others including recombinant relaxin-2 and vasopressin antagonists. This article will review posited mechanisms of heart failure, and highlight novel therapeutic options in the pediatric population.